Challenges in astroparticles - Siqueira, Clarissa (Cadernos de Astronomia, 2026)
Astroparticle physics plays a central role in addressing fundamental questions in modern physics by connecting particle physics, cosmology, and astrophysics. Among the main problems, we highlight the nature of dark matter and dark energy, primordial inflation, the matter-antimatter asymmetry of the universe, and the origin of ultra-high-energy cosmic messengers. In this article, we review the main observational evidence for dark matter, which spans scales from galactic to cosmological, and discuss the two most explored scenarios for its nature: primordial black holes and new fundamental particles beyond the Standard Model. We explore the main theoretical and experimental bottlenecks that challenge the search for the nature of dark matter, highlighting those associated with extended mass distributions of primordial black holes and the absence of weakly interacting massive particle signals in direct, indirect, and accelerator detection experiments. We also discuss the role of next-generation experiments, including very high-energy gamma-ray telescopes and multi-messenger detectors. Finally, we conclude that the combination of high-precision observations and theoretical advances will be crucial to elucidating the microphysics of dark matter and deepening our understanding of the extreme universe.